Awareness regarding diabetes complications among patients with diabetes in a tertiary hospital - Devaka Kumari Acharya,; Binita Sigdel,; Anil Bhattarai, (Journal of Universal College of Medical Sciences, 2026)
INTRODUCTIONPeople with diabetes mellitus have a high risk of several serious health problems that increase healthcare costs, decrease life quality, and increase the death rate. The study aimed to assess the awareness regarding diabetic complications among patients with diabetes.MATERIAL AND METHODSA descriptive cross-sectional study was conducted in the Endocrine Outpatient Department of Tribhuvan University Teaching Hospital, Kathmandu, Nepal. A total of 101 patients diagnosed with diabetes were selected using purposive sampling. Data were collected through face-to-face interviews with structured interview questionnaires in the Outpatient Department before and or after medical checkups. Data were entered in SPSS version 16 and analyzed using descriptive statistics for frequency, percent, median, mean, and interquartile range, and inferential statistics Chi-square to measure the association between awareness of diabetic complications and sociodemographic and disease-related variables.RESULTSMore than half (56.4%) of the respondents had an adequate level of awareness and more than two-fifths (43.6) of the respondents had an inadequate level of awareness on complications of diabetes. Awareness of complications of diabetes was significantly associated with duration of diabetes (p=0.05) and experience of diabetes complications (p=0.03).CONCLUSIONThis study concludes that nearly half of diabetic patients have inadequate awareness on complications of their disease. To decrease the onset of diabetic complications and financial burden to the patients and healthcare system and increase the patients’ quality of life diabetic awareness programs are required to be conducted at the community and health institution level.